Graphene‐Based Mesoporous SnO2 with Enhanced Electrochemical Performance for Lithium‐Ion Batteries. (18th February 2013) - Yang, Sheng; Yue, Wenbo; Zhu, Jia; Ren, Yu; Yang, Xiaojing
Abstract Graphene‐based metal oxides generally show outstanding electrochemical performance due to the superior properties of graphene. However, the aggregation of active metal oxide nanoparticles on the graphene surface may result in a capacity fading and poor cycle performance. Here, a mesostructured graphene‐based SnO2 composite is prepared through in situ growth of SnO2 particles on the graphene surface using cetyltrimethylammonium bromide as the structure‐directing agent. This novel mesoporous composite inherits the advantages of graphene nanosheets and mesoporous materials and exhibits higher reversible capacity, better cycle performance, and better rate capability compared to pure mesoporous SnO2 and graphene‐based nonporous SnO2. It is concluded that the synergetic effect between graphene and mesostructure benefits the improvement of the electrochemical properties of the hybrid composites. This facile method may offer an attractive alternative approach for preparation of the graphene‐based mesoporous composites as high‐ performance electrodes for lithium‐ion batteries.